Eksekusi Jaminan Oleh Debt Collector Sebagai Akibat Wanprestasi Dalam Perjanjian Fidusia - Ronald Fadly Sopamena (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2021)
Debt is something that is common in today's society. The level of income that is not proportional to the level of need is the reason why someone has to go into debt. Among the existing debt facilities, fiduciary is one of the most popular institutions in the community. But fiduciary itself is not without a problem. There are often forced withdrawals made by debt collectors who do not hesitate to use violence both physically and verbally on debtors who are in arrears in paying their installments. The research method used is normative juridical or what is known as legal research which is carried out by reviewing and analyzing the substance of legislation on the subject matter or legal issue in its consistency with existing legal principles. The result of the research is that finance companies are allowed to use the services of a third party by entering into a cooperation agreement that is contained in a stamped written agreement. The third party who collects is a legal entity that has permission from the competent authority and human resources who already have a professional certificate in the field of billing from an institution appointed by the association of Indonesian finance companies. In carrying out their duties as the party executing the fiduciary guarantee, the debt collector must meet several conditions. debt collectors are required to bring a number of documents such as identity cards, letters of assignment from finance companies, proof of debtor default documents, copies of fiduciary guarantee certificates. In addition, collection officers are required to bring a professional certificate in the field of billing from a professional certification agency in the field of financing registered with the Financial Services Authority.